Structuralism and Levi Strauss (Journal of Human Sciences, 2020)
This searching involves study of the structuralism engender through study mean of structuralism, Naturalists, condition of Engenders and Knowing the famous Philosophy. concerns  on analysis the vision that courteousness  by the French elder structuralism Philosophy Levi Strauss through Known the backdrop since that was as Guide to him this analysis based on the following points ..Indicate to manner of analysis study to many of human structural access to milestones structuralism manner and most important characters.